EVALUATION OF TRAFFIC MANAGEMENT AT PORT CROSSING GILIMANUK - Siti Nurlaili Triwahyuni; Elfita Agustini; Ni Komang Budiantini (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
Traffic management at the port is very important to create order, regularity, and smooth or comfortable activities in the harbor transport through the implementation of a zoning system and traffic management in accordance with applicable regulations. However, the implementation of zoning is still not optimal because there are still hawkers around the port and the occurrence of crossings between vehicles which makes service users uncomfortable and the flow pattern at the port is not smooth so that it can cause congestion. The method in this research is descriptive qualitative with several approaches in obtaining data as reference and comparison material to describe the state of the object under study in accordance with the situation and conditions when the research was conducted. Based on the analysis results obtained, the zoning system has not been implemented in accordance with the Regulation of the Minister of Transportation Number 29 of 2016 concerning Fertilization of Ferry Ports and there are still crossings between vehicles that will enter and leave the ship. From the results of the analysis, it is necessary to rearrange traffic management and apply the zoning system in accordance with applicable regulations.